Assessing environmental change and population declines of large wading birds in southwestern India - K.M. Aarif; Aymen Nefla; K.A. Rubeena; Yanjie Xu; Zakher Bouragaoui; M. Nasser; C.T. Shifa; T.R. Athira; K. Jishnu; Jasmine Anand; Seerangan Manokaran; P.P. Moosa; et al. (Environmental and Sustainability Indicators)
Large waders including herons and egrets are important ecological wetland health indicators since these species are sensitive to a complex set of environmental factors. Anthropogenic factors are driving major changes in coastal and inland wetlands. We investigated the relationship between environmental variables, productivity, fish diversity and large waders in southwestern India. These variables cover climatic variables (rainfall), sediment variables (salinity, pH, organic carbon, nitrogen, phosphorus), water variables (Salinity, pH, temperature, nitrate, phosphate), primary productivity (Chlorophyll-a) and prey availability (mean fish stock availability). Densities of all the studied wader species decreased significantly from 2010 to 2019, with highest densities in agroecosystems or estuarine habitats and in post-monsoon seasons but lowest in mudflats and in monsoon seasons. Structural equational modelling revealed that rainfall and organic carbon positively affected the primary productivity, whereas water variables (nitrate, salinity and phosphate) positively affected the fish stock availability. This in turn positively affected the density of large wading birds. The decreasing trend of water nitrate negatively affected the primary productivity and density of waterbirds while rainfall negatively affected fish stock availability and waterbird density. Sediment phosphorous adversely affected both the biotic variables and the density of waterbirds. Sediment variables (salinity, pH, and phosphorus) increased over years, whereas organic carbon and nitrogen in the sediment decreased significantly. Salinity, water temperature, pH, and phosphate showed a significant increase while water nitrate, and chlorophyll-a decreased over the period of study. Significant decline in fish stock availability and altered environmental variables resulted in long term decline in the abundance of wading birds. Thus, large waders have adapted to these long-term, anthropogenically driven, environmental changes by shifting to agroecosystems and estuaries as their alternate foraging habitats. These population declines indicate consistent decline in ecosystem health of wetlands. Strategies need to be formulated to mitigate declines and restore ecosystem health.